Fetal cardiovascular hemodynamics in type 1 diabetic pregnancies at near-term gestation - Lehtoranta Lara; Haapsamo Mervi; Vuolteenaho Olli; Palo Pertti; Ekholm Eeva; Räsänen Juha (WILEY, 2022)
Introduction
Poor glycemic control in maternal type 1 diabetes mellitus during pregnancy can affect fetal cardiac and placental function. However, studies concerning fetal central hemodynamics have revealed conflicting results. We hypothesized that in pregnancies complicated by maternal type 1 diabetes, fetal cardiovascular and placental hemodynamics are comparable to the control fetuses at near-term gestation. In addition, we investigated the relationship between newborn serum biomarkers of cardiac function and fetal cardiovascular and placental hemodynamics. Furthermore, we studied whether maternal diabetes is associated with placental inflammation.
Material and methods
In this prospective case-control study, fetal central and peripheral hemodynamics were assessed by ultrasonography in 33 women with type 1 diabetes and in 67 controls with singleton pregnancies between 34(+2)and 40(+2)gestational weeks. Newborn umbilical cord serum was collected to analyze cardiac natriuretic peptides (atrial and B-type natriuretic peptides) and troponin T concentrations. Placental tissue samples were obtained for cytokine analyses.
Results
Fetal ventricular wall thicknesses were greater and weight-adjusted stroke volumes and cardiac outputs were lower in the type 1 diabetes group than in the control group. Pulsatility in the aortic isthmus and inferior vena cava blood flow velocity waveforms was greater in the type 1 diabetes group fetuses than in the controls. A positive correlation was found between branch pulmonary artery and aortic isthmus pulsatility index values. Umbilical artery pulsatility indices were comparable between the groups. Umbilical cord serum natriuretic peptide and troponin T concentrations were elevated in the type 1 diabetes fetuses. These cardiac biomarkers correlated significantly with cardiovascular hemodynamics. Placental cytokine levels were not different between the groups.
Conclusions
In maternal type 1 diabetes pregnancies, fetal cardiovascular hemodynamics is impaired. Maternal type 1 diabetes does not seem to alter placental vascular impedance or induce placental inflammation.